Conciencia ambiental y comportamiento ecológico en los estudiantes del 2do grado de secundaria de la I.E Santo Toribio - Sandoval Padilla, Aracelli Trinidad (2016)
The present investigation: Environmental Conscience and eco/ogical behavíor in the student's of the second secondary educatíonal grade of her Institución Educativa Santo Toribio in the 2014, has to determine the relation among the conscience environmental purpose and her ecological behavior of the student's of the second secondary- educational grade Institución Educativa Santo Toribio in the 2014 . . Specific objectives atended: Examining the environmental, leve! individual worry, social worry, confidence conscience and criteria in the students of the second secondaryeducation grade of her Institución Educativa Santo Toribio, in the 2014; identifying the behavioral fellow ecological in the urban- cleanliness dimensions, 1 save of water and energy , activism 1 consume and her recycling of the students of the second secondaryeducational grade Institución Educativa Santo Toribio, in the 2014 and establishing the relation among environmental conscience and ecological behavior in the student's of the second secondary educational grade of her Institución Educativa Santo Toribio, in the 2014 Environmental conscience is held in Alvarado's supposed theorists (2009), He alloys (2006), Corraliza (2004); And the ecological behavior in Suarez (2000), Corral (2000), Pato and T a mayo (2006). They give the enough theoretic toots to present the following positive relation Exists significant enter environmental conscience and ecological behavior in the student's of the second secondary- educational grade of her Institución Educativa Santo Toribio in the year 2014. Methodolgy the fact-finding design was Transaccional Correlaciona!, with 95 student's sign of her Institución Educativa Santo T oribio and it was obtained that the central or tactfinding hypothesis with the 95 confidence is accepted in the sta\istical analysis process, the same one that evidences itself in the graphic of the curve of Gauss and. in the value that they have obtained me in of the correlation coefficient of Pearson r s = o, 7693 being a positive correlation.